HUBUNGAN ANTARA KEPUASAN KERJA DENGAN KINERJA PADA FIELD FORCE PT. ANUGRAH ARGON MEDICA SEMARANG - Citra Kusumaningtyas; Alice Zellawati; Brigitan Argasiam (IMAGE, 2021)
This research aims to empirically test the relationship between job satisfaction and the performance of Field Force employees at PT ANUGRAH ARGON MEDICA Semarang. The sample for this research was the PT ANUGRAH ARGON MEDICA field force team in Semarang and its surroundings, namely 91 people. The sampling technique used was purposive sampling. Data analysis uses Spearman Correlation. The research results show that there is a positive relationship between job satisfaction and employee performance as indicated by the correlation value rs = +0.410 with significance = 0.000 (p < 5%). This research also shows that there is no difference in performance between male and female employees as indicated by sig = 0.365 (p > 5%) but on the contrary there is a difference in job satisfaction between male and female employees as indicated by sig = 0.011 (p < 5%) where male employees show higher job satisfaction than female employees, especially in the field force. Apart from that, the results of this study also found that there was no relationship between length of service and employee work placement with the level of performance and job satisfaction felt with sig. > 5%. Keywords : Performance, Job satisfaction